Numerical simulation model by volume averaging for the dissolution process of GaSb into InSb in a sandwich system. (1st November 2016) - Yamamoto, Takuya; Mirsandi, Haryo; Jin, Xin; Takagi, Youhei; Okano, Yasunori; Inatomi, Yuko; Hayakawa, Yasuhiro; Dost, Sadik
ABSTRACT: The volume-averaging continuum technique has been utilized to obtain numerical predictions for the transport phenomena occurring during the dissolution process of GaSb into InSb melt in a sandwich system. Dissolution and subsequent growth in this system are achieved by the application of a temperature gradient. The developed model was first verified for two test cases [(i) fluid/solid conjugate heat transfer and (ii) the solidification process of the binary system]. The code was then utilized to simulate the dissolution process of GaSb into InSb in the GaSb/InSb/GaSb sandwich system. The present results show that the developed volume-averaging model provides accurate predictions.